'Humorous financial crisis cartoons': A visual essay of an elementary school art project. (1st March 2017) - Christopoulou, Martha
This visual essay reports on the first part of an eight-week resilience art programme at a public primary school in Athens, Greece. The students were asked to create humorous cartoons as a response to the financial crisis. Humour as coping mechanism can defuse tension and anxiety and may lead to more positive re-appraisals of the financial crisis and as such contribute to developing children's resilience.